2021
DOI: 10.7717/peerj.11883
|View full text |Cite
|
Sign up to set email alerts
|

HepGentox: a novel promising HepG2 reportergene-assay for the detection of genotoxic substances in complex mixtures

Abstract: Background In risk assessment, genotoxicity is a key factor to determine the safety for the consumer. Most in vitro genotoxicity assays were developed for the assessment of pure substances. However, in recent years more attention has been given to complex mixtures, where usually low amounts of a substance are present. For high-throughput screening, a toxicologically sensitive assay should be used, covering a broad range of genotoxic substances and detecting them at low concentrations. HepG2 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…Importantly, a broad introduction of false positive artefacts, e.g., through contamination with the amino acid histidine originating from protein residues of packed food, could be ruled out, as genotoxicity was confirmed by additional in vitro bioassays targeting a different mode of action. For that, a HepGentox assay based on the p53 pathway [31] and an umuC test based on the SOS pathway [32] were used to test selected recyclate extracts. A Petri-dish-based Ames test (based on OECD guideline 471 [26]) with selected samples confirmed that the DNA-reactive behavior was independent of the miniaturized format applied here.…”
Section: Interpretation Of the Miniaturized Ames Test Resultsmentioning
confidence: 99%
“…Importantly, a broad introduction of false positive artefacts, e.g., through contamination with the amino acid histidine originating from protein residues of packed food, could be ruled out, as genotoxicity was confirmed by additional in vitro bioassays targeting a different mode of action. For that, a HepGentox assay based on the p53 pathway [31] and an umuC test based on the SOS pathway [32] were used to test selected recyclate extracts. A Petri-dish-based Ames test (based on OECD guideline 471 [26]) with selected samples confirmed that the DNA-reactive behavior was independent of the miniaturized format applied here.…”
Section: Interpretation Of the Miniaturized Ames Test Resultsmentioning
confidence: 99%